USE THE ULTRASONIC SCALPEL IN STOMACH SURGERY - Khvorostov, E.D.; Tomin, M.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The results of experimentaland clinical application of ultrasonic scalpel are analysed at implementation of operations on a stomach. In an experiment there were 70 rabits of breed Chinchilla. An ultrasonic scalpel was utillized in the basicgroup of animals (n=35), in control (n=35) is a monoarctic electro-knife (MEN). In clinical part patients with the surgical diseases of stomach (n=111) parted on two groups. In a basic group (n=46) operative interferences were executed by USS, in control (n=65) – with MEN. Morphological changes, what be going on under the action of physical types of energy, are studied. It is set that ultrasonic dissection does not render the serious damaging affecting gastric wall, and a section takes a place quickly and bloodless. On the basis of findings an ultrasonic scalpel is recommended for forming of gastroenteroanastomosis in clinical terms.